Exploring Contributing Factors in Psychological Contract Formation - Frost, Leanne (New Zealand Journal of Health and Safety Practice, 2025)
Abstract Introduction: This review explored factors that influence the formation of psychological contracts. These are implicit, unspoken expectations employees develop about their employer’s obligations based on perceived promises and organisational values. Methods: A targeted search of Emerald, SCOPUS, and ProQuest was conducted using Boolean operators and truncation, with date limits set from 2015 to 2025. Articles were screened and appraised using the Mixed Methods Appraisal Tool to ensure quality across diverse methodologies. Findings: Employer branding, organisational website benefits, and information received during the orientation and onboarding stages of employment were found to contribute to the formation of psychological contracts. Psychological contracts were found to form in multiple contexts, including diverse cultures, organisational settings, and for-profit and not-for-profit environments. Conclusion: This review highlights how psychological contracts are shaped by both organisational branding and early social interactions. By identifying the factors that influence their formation, organisations can take proactive steps to clarify and articulate expectations, helping to reduce strain in workplace relationships and thus manage psychosocial risk.